Schauplatz Archiv Objekt – Narrativ – Performanz - Kastberger, Klaus; Maurer, Stefan; Neuhuber, Christian (2019)
While archives have traditionally attracted little publicity, this situation is in flux: things that were hidden away – from precious objects to curiosities – are now being made available not only to scholars but to a broader public audience as well. This volume addresses questions related to the accessibility, representation, and dissemination of institutionally preserved cultural heritage.